ANALYSIS OF THE EFFECTS OF PERCEIVED BENEFIT AND PERCEIVED EASE ON CONSUMER INTEREST IN USING SINGLE TRIP TICKET OF MRT JAKARTA AND THE IMPACT ON BUYING DECISION - Ayuverda, Kadita; Dudi Permana (Dinasti International Journal of Management Science, 2020)
The purpose of the present study was determining the result of Analysis of the Effects of Perceived Benefit and Perceived Ease on Consumer Buying Interest in Single Trip Ticket of MRT Jakarta and the Impact on Buying Decision. The present study used descriptive research design with survey method. Sampling used purposive sampling technique. The present study was tested using structural equation modeling – Lisrel to examine the effect of significance of the entire model and preset path. The finding showed that Perceived Benefit and Perceived Ease significantly affected Consumer Buying Interest. The present study also showed that Consumer Buying Interest affected Buying Decision. The company should improve Perceived Benefit and Perceived Ease.